High-throughput vibrational spectroscopy methods for determination of degree of acetylation for chitin and chitosan. (15th February 2023) - Rehman, Hafeez Ur; Cord-Landwehr, Stefan; Shapaval, Volha; Dzurendova, Simona; Kohler, Achim; Moerschbacher, Bruno M.; Zimmermann, Boris
Abstract: The rising demand for chitin and chitosan in chemical, agro-food, and healthcare industries is creating a need for rapid and high-throughput analysis. The physicochemical properties of these biopolymers are greatly dependent on the degree of acetylation (DA). Conventional methods for DA determination, such as LC-MS and 1 H NMR, are time-consuming when performed on many samples, and therefore efficient methods are needed. Here, high-throughput microplate-based FTIR and FT-Raman methods were compared with their manual counterparts. Partial least squares regression models were based on 30 samples of chitin and chitosan with reference DA values obtained by LC-MS and 1 H NMR, and the models were validated on an independent test set of 16 samples. The overall predictive accuracy of the high-throughput methods was at the same level as the manual methods and the well-established LC-MS and 1 H NMR methods. Therefore, high-throughput FTIR and FT-Raman DA determination methods have great potential to serve as fast and economical substitutes for traditional methods. Graphical abstract: Unlabelled Image